The Role of Productive Capacity Pillars in CO2 Emissions: How does their Interaction Matter in the MENA Region? - Daghbagi, Hamrouni; Ouerghi, Imen; Hasni, Radhouane (International Journal of Energy Economics and Policy, 2025)
Analysis of productive capacity is essential for inclusive and sustainable growth and can influence environmental quality. This is particularly relevant for the MENA region, characterized by high fossil fuel dependence and climate vulnerability. This study fills a gap by analyzing the direct effects and interactions of the three productive capacity pillars on CO₂ emissions in MENA. It examines the impact of natural capital (NC), information and communication technology (ICT), and institutional quality (IQ) on CO₂ emissions (2000–2021) using the ARDL-PMG model and causality analysis. Control variables include GDP, renewable, and non-renewable energy consumption. Results show that ICT and IQ reduce emissions, but their interaction with NC increases them due to oil dependence. However, ICT-IQ interaction offers potential for emission reduction. GDP growth and non-renewable energy increase emissions, while underdeveloped renewable energy helps reduce them. Our findings provide insights for policymakers to enhance productive capacity while promoting sustainable development.